Different pig slurry application methods modify the soil quality and increase the productivity of winter wheat (Triticum aestivum L.) Crop (Córdoba, Argentina) = Diferentes métodos de aplicação de dejectos líquidos de suínos modificam a qualidade do solo e aumentam a produtividade da cultura de trigo de inverno (Triticum aestivum L.) (Córdoba, Argentina) - Pegoraro, Vanesa Romina; Mir, Leticia Raquel; Briacchi, Martina; Bachmeier, Omar; Ortiz, Jimena; Lorenzon, Claudio Antonio; Hang, Susana; Zubillaga, Marta Susana (Brazilian Journals Publicações de Periódicos e Editora, 2022)
In Argentina, slurry surface application is the technique most used, although with high risk of ammonia losses. These emissions can be reduced by using different application methods, but their impacts on the soil-plant system have been little explored. Thus, this study aimed to evaluate the effects of different pig slurry application methods: acidified slurry (AS), incorporated slurry (IS), and surface slurry (SS) on the soil quality and productivity of a wheat crop, as compared with mineral fertilization (MF) and control (C). IS caused an increase in acid phosphatase values, whereas SS presented the lowest metabolic quotient values of all methods and high values of fluorescein diacetate hydrolysis. Treatments with pig slurry and MF showed significantly lower pH values than C. SS led to a rapid increase in NO3-concentration, whereas AS and IS showed slower nitrification values than SS. Depending on the availability of NO3-, N uptake and aerial biomass showed a similar behavior. Wheat yield increased up to 57% with pig slurry application, without significant differences between the different application methods used. However, MF reached the highest yield value. We conclude that pig slurry application, mainly surface application, improves soil quality and increases wheat production.